Highly ion-conductive solid electrolyte membrane, its manufacturing method and all-solid-state battery including the same
By optimizing the packing density and ionic conductivity of the solid electrolyte membrane through the use of sulfide-based or halide-based solid electrolytes and high-temperature pressurization of the binder, the limitations of existing solid electrolytes in all-solid-state batteries are addressed, leading to enhanced battery performance and safety.
Patent Information
- Application Number
- JP2024550613
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-01-25
- Filing Date
- 2024-01-25
- Publication Date
- 2025-03-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing solid electrolytes in all-solid-state batteries face limitations in ionic conductivity, which affects the safety and performance of these batteries.
A solid electrolyte membrane with a packing density of 0.81 to 0.99 is developed, using a sulfide-based or halide-based solid electrolyte and a binder, where the binder is pressurized at a temperature above its glass transition temperature to enhance packing density and ionic conductivity.
The improved packing density and ionic conductivity of the solid electrolyte membrane enhance the performance and safety of all-solid-state batteries, allowing for wider application fields.
Smart Images

Figure 2025507716000001_ABST
Abstract
Description
[Technical field]
[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2023-0009548 dated January 25, 2023, and all contents disclosed in the documents of said Korean patent application are incorporated herein by reference.
[0002] The present invention relates to a high ion-conductive solid electrolyte membrane, a method for producing the same, and an all-solid-state battery including the same. [Background technology]
[0003] From the viewpoints of battery capacity, safety, output, large size, ultra-compactness, and the like, various batteries capable of overcoming the limitations of lithium secondary batteries are currently being researched.
[0004] Representatively, research is being continuously conducted in academia and industry into metal-air batteries, which have a much larger theoretical capacity than lithium secondary batteries, all-solid-state batteries, which are safe and have no risk of explosion, supercapacitors in terms of output, NaS batteries or RFB (redox flow batteries) in terms of large size, and thin film batteries in terms of ultra-miniaturization.
[0005] An all-solid-state battery is a battery that replaces the liquid electrolyte used in conventional lithium secondary batteries with a solid, and can significantly improve safety by not using flammable solvents in the battery and completely eliminating the risk of fire or explosion caused by the decomposition reaction of conventional electrolytes. In addition, because Li metal or Li alloy can be used as the anode material, it has the advantage of dramatically improving the energy density relative to the mass and volume of the battery.
[0006] However, although the use of the solid electrolyte in the all-solid-state battery can ensure safety, there is a possibility that the ionic conductivity may decrease, and if a liquid electrolyte is used together with the solid electrolyte to ensure the ionic conductivity of the solid electrolyte, there is a problem that the strength decreases.
[0007] In general, in order to prevent deterioration of the performance and processability of an all-solid-state battery, the ionic conductivity of the solid electrolyte must be maintained at a certain level or higher.
[0008] Therefore, research and development is ongoing to improve the ionic conductivity of solid electrolytes. As the demand for and application fields of all-solid-state batteries increase, the level of ionic conductivity required for solid electrolytes is also increasing. However, there is a limit to the ionic conductivity of commercialized solid electrolytes, and there is a limit to the fields in which all-solid-state batteries including solid electrolytes can be applied.
[0009] Therefore, there is a need to develop a solid electrolyte having a level of ionic conductivity that can be applied to a wider variety of fields. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] Korean Patent Publication No. 2022-0095689 Summary of the Invention [Problem to be solved by the invention]
[0011] The present inventors have conducted extensive research to solve the above problems, and have found that a solid electrolyte membrane manufactured by coating a substrate with a slurry containing a sulfide-based and / or halide-based solid electrolyte, a binder, and a solvent, followed by drying and pressing at a temperature equal to or higher than the glass transition temperature (Tg) of the binder has a high packing density and improved ionic conductivity.
[0012] It is therefore an object of the present invention to provide a solid electrolyte membrane having improved ionic conductivity and a method for producing the same.
[0013] It is another object of the present invention to provide an all-solid-state battery including a solid electrolyte membrane with improved ionic conductivity. [Means for solving the problem]
[0014] In order to achieve the above object, the present invention provides a solid electrolyte membrane comprising a solid electrolyte and a binder, the solid electrolyte comprising at least one selected from the group consisting of a sulfide-based solid electrolyte and a halide-based solid electrolyte, and having a packing density of 0.81 to 0.99.
[0015] The present invention also provides a solid electrolyte membrane, wherein the sulfide-based solid electrolyte is represented by the following chemical formula 1:
[0016] [Chemical formula 1] L a1 M b1 P c1 S d1 A e1 In the above Chemical Formula 1, L is an element selected from Li, Na, and K, M is an element selected from B, Zn, Sn, Si, Cu, Ga, Sb, Al, and Ge, A is I, Br, Cl, or F, a1 to e1 are composition ratios of each element, and a1:b1:c1:d1:e1 is 1-12:0-1:1:2-12:0-5.
[0017] The present invention also provides a solid electrolyte membrane, wherein the halide-based solid electrolyte is represented by the following chemical formula 2:
[0018] [Chemical formula 2] Li 6-3a M a Br b Cl c In the above formula 1, M is a metal other than Li, and a is 0. <a<2であり、bは0≦b≦6であり、cは0≦c≦6であり、b+c=6である。
[0019] The present invention also provides a solid electrolyte membrane, wherein the solid electrolyte is contained in an amount of 95 to 99.5% by weight based on the total weight of the solid electrolyte membrane.
[0020] The present invention also provides a solid electrolyte membrane, wherein the binder comprises at least one selected from the group consisting of ethylene-vinyl acetate (EVA), styrene-ethylene-butylene-styrene (SEBS), styrene butadiene rubber (SBR), nitrile butadiene rubber (NBR), hydrogenated nitrile butadiene rubber (HNBR), and copolymers containing any of the above.
[0021] The present invention also provides a solid electrolyte membrane, wherein the binder is contained in an amount of 0.5 to 5% by weight based on the total weight of the solid electrolyte membrane.
[0022] The present invention also provides a solid electrolyte membrane, in which the solid electrolyte is directly bonded to an adjacent solid electrolyte or is bonded to an adjacent solid electrolyte via the binder.
[0023] The present invention also provides a solid electrolyte membrane, wherein the solid electrolyte membrane has an ion conductivity of 0.1 to 10 mS / cm.
[0024] The present invention also provides a method for manufacturing a semiconductor device comprising the steps of: (S1) mixing a solid electrolyte, a binder, and a solvent to form a slurry; (S2) coating the slurry on a substrate and then drying it; and (S3) compressing the coating layer at a temperature equal to or higher than the glass transition temperature (Tg) of the binder; The present invention provides a method for producing a solid electrolyte membrane, wherein the solid electrolyte includes at least one selected from the group consisting of a sulfide-based solid electrolyte and a halide-based solid electrolyte.
[0025] The present invention also relates to a method for preparing a solvent comprising the steps of: The aprotic solvent includes at least one selected from the group consisting of anisole, xylene, toluene, N,N'-dimethylacetamide (DMAc), N-methyl pyrrolidone (NMP), dimethyl sulfoxide (DMSO), and N,N-dimethylformamide (DMF).
[0026] The present invention also provides a method for producing a solid electrolyte membrane, wherein the binder has a glass transition temperature (Tg) of 45 to 250°C.
[0027] The present invention also provides a method for producing a solid electrolyte membrane, wherein the pressure during the pressurization is 300 to 500 MPa.
[0028] The present invention also provides an all-solid-state battery comprising a positive electrode, a negative electrode, and the solid electrolyte membrane interposed between them. Effect of the Invention
[0029] According to the present invention, in a wet process for manufacturing a solid electrolyte membrane, a slurry containing a solid electrolyte, a binder, and a solvent is coated on a substrate, dried, and then compressed. By applying pressure at a temperature equal to or higher than the glass transition temperature (Tg) of the binder, the packing density of the solid electrolyte membrane can be increased and ionic conductivity can be improved. [Brief description of the drawings]
[0030] [Figure 1] 1A to 1C are schematic diagrams illustrating a process for manufacturing a solid electrolyte membrane according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0031] The present invention will now be described in further detail to aid in the understanding of the present invention.
[0032] The terms and words used in this specification and claims should not be interpreted in a limited manner to their ordinary or dictionary meanings, but should be interpreted in a meaning and concept that corresponds to the technical idea of the present invention, based on the principle that an inventor can appropriately define the concept of a term in order to best describe his / her invention.
[0033] As used herein, the term "packing density" refers to the ratio of the volume excluding pores to the total volume of the solid electrolyte membrane.
[0034] solid electrolyte membrane The present invention relates to a solid electrolyte membrane.
[0035] The solid electrolyte membrane according to the present invention includes a solid electrolyte and a binder, and the solid electrolyte includes at least one selected from the group consisting of sulfide-based solid electrolytes and halide-based solid electrolytes, and has a packing density of 0.81 to 0.99. Specifically, the packing density may be 0.81 or more, 0.83 or more, or 0.85 or more, or 0.97 or less, 0.98 or less, or 0.99 or less.
[0036] The solid electrolyte membrane according to the present invention contains particulate solid electrolyte and binder at a high packing density due to a high temperature and pressure process during the manufacturing process.
[0037] During the preparation of the solid electrolyte membrane, the fluidity of the binder is increased by the high temperature above the glass transition temperature (Tg) of the binder in the pressurizing process, and the packing between the solid electrolyte particles or between the binders is increased by the applied pressure, thereby improving the packing density and ionic conductivity of the solid electrolyte membrane.
[0038] In one embodiment of the present invention, the packing density of the solid electrolyte membrane may be 0.81 to 0.99. If the packing density is less than 0.81, the ion conductivity of the solid electrolyte membrane may be reduced, and if the packing density is more than 0.99, the process cost during the manufacture of the all-solid-state battery may increase.
[0039] In one embodiment of the present invention, the ionic conductivity of the solid electrolyte membrane may be 0.1 to 10 mS / cm. The ionic conductivity may be measured at room temperature (25° C.). Specifically, the ionic conductivity may be 0.1 mS / cm or more, 0.3 mS / cm or more, 0.5 mS / cm or more, or 0.7 mS / cm or more, and may be 2 mS / cm or less, 4 mS / cm or less, 6 mS / cm or less, 8 mS / cm or less, or 10 mS / cm or less.
[0040] In an embodiment of the present invention, the solid electrolyte may include a sulfide-based solid electrolyte and / or a halide-based solid electrolyte.
[0041] The solid electrolyte may be contained in an amount of 95 to 99.5 wt % based on the total weight of the solid electrolyte membrane, and specifically, the content of the solid electrolyte may be 95 wt % or more, 96 wt % or more, 97 wt % or more, or 98 wt % or more, or 99.1 wt % or less, 99.3 wt % or less, or 99.5 wt % or less. If the content of the solid electrolyte is less than 95 wt %, the ionic conductivity of the solid electrolyte membrane may be low, and if it exceeds 99.5 wt %, the content of the binder may be relatively reduced, and the tensile strength may be somewhat reduced.
[0042] The solid electrolyte may be particulate and its particle size (D50) may be 10 nm to 10 μm, specifically, 10 nm or more, 100 nm or more, 1 μm or more, 2 μm or more, or 3 μm or more, and 5 μm or less, 7 μm or less, 9 μm or less, or 10 μm or less. If the particle size (D50) of the solid electrolyte is less than 10 nm, the tensile strength may decrease, and if it exceeds 10 μm, the surface of the solid electrolyte membrane may not be uniform, and the resistance with the electrodes may increase.
[0043] In one embodiment of the present invention, the sulfide-based solid electrolyte may be represented by the following Chemical Formula 1:
[0044] [Chemical formula 1] L a1 M b1 P c1 S d1 A e1 In the above Chemical Formula 1, L is an element selected from Li, Na, and K, M is an element selected from B, Zn, Sn, Si, Cu, Ga, Sb, Al, and Ge, A is I, Br, Cl, or F, a1 to e1 are composition ratios of each element, and a1:b1:c1:d1:e1 is 1-12:0-1:1:2-12:0-5.
[0045] For example, the sulfide-based solid electrolyte may include at least one selected from the group consisting of LiPSX (X=Cl, Br, or I), LiGePS, and LiPS. However, the sulfide-based solid electrolyte is not limited thereto, and a wide range of sulfide-based solid electrolytes commonly used in the art may be used.
[0046] In one embodiment of the present invention, the halide-based solid electrolyte may be represented by the following Chemical Formula 2:
[0047] [Chemical formula 2] Li 6-3a M a Br b Cl c In the above formula 1, M is a metal other than Li, and a is 0. <a<2であり、bは0≦b≦6であり、cは0≦c≦6であり、b+c=6である。
[0048] For example, the halide-based solid electrolyte may include one or more selected from the group consisting of Li3YBr6, Li3YCl6, and Li3YBr2Cl4.
[0049] In one embodiment of the present invention, the binder is pressurized at a temperature equal to or higher than the glass transition temperature (Tg) during the manufacturing process to increase the mobility thereof, thereby increasing the adhesive force between solid electrolyte particles and improving the packing density of the solid electrolyte membrane.
[0050] The binder may be at least one selected from the group consisting of ethylene-vinyl acetate (EVA), styrene-ethylene-butylene-styrene (SEBS), styrene butadiene rubber (SBR), nitrile butadiene rubber (NBR), hydrogenated nitrile butadiene rubber (HNBR), and copolymers containing the same, but is not limited thereto.
[0051] The binder may be included in an amount of 0.5 to 5 wt % based on the total weight of the solid electrolyte membrane. Specifically, the binder content may be 0.5 wt % or more, 0.7 wt % or more, or 0.9 wt % or more, and 2 wt % or less, 3 wt % or less, 4 wt % or less, or 5 wt % or less. If the binder content is less than 0.5 wt %, the improvement in packing density of the solid electrolyte membrane is small, and the improvement effect of ion conductivity is negligible, and if it exceeds 5 wt %, it may act as resistance and rather reduce ion conductivity.
[0052] In one embodiment of the present invention, the thickness of the solid electrolyte membrane may be 50 to 150 μm. Specifically, the thickness of the solid electrolyte membrane may be 50 μm or more, 60 μm or more, 70 μm or more, or 80 μm or more, and may be 120 μm or less, 130 μm or less, 140 μm or less, or 150 μm or less. If the thickness of the solid electrolyte membrane is less than 50 μm, the strength of the membrane may be low and the processability may be reduced, and if the thickness exceeds 150 μm, the energy density may be reduced.
[0053] Method for producing solid electrolyte membrane The present invention also relates to a method for producing the solid electrolyte membrane.
[0054] FIG. 1 is a schematic diagram showing a process for producing a solid electrolyte membrane according to one embodiment of the present invention.
[0055] 1, the method for producing a solid electrolyte membrane (1) according to the present invention includes steps of (S1) mixing a solid electrolyte (10), a binder (20) and a solvent to form a slurry (not shown); (S2) coating the slurry on a substrate (30) and drying it (Coating & Drying); and (S3) pressing the coating layer at a temperature equal to or higher than the glass transition temperature (Tg) of the binder (20). The solid electrolyte includes at least one selected from the group consisting of sulfide-based solid electrolytes and halide-based solid electrolytes. The types and contents of the solid electrolyte and binder are the same as those described above.
[0056] When the pressure is applied at a high temperature rather than at a low temperature, the physical space between the solid electrolyte 10 and the binder 20 in the produced solid electrolyte membrane 1 becomes denser, resulting in a higher packing density. In this case, the high temperature may be a temperature equal to or higher than the glass transition temperature (Tg) of the binder.
[0057] Hereinafter, each step of the method for producing a solid electrolyte membrane according to the present invention will be described in detail.
[0058] In the method for preparing a solid electrolyte membrane according to the present invention, in step (S1), a solid electrolyte, a binder, and a solvent may be mixed to form a slurry.
[0059] The types and contents of the solid electrolyte and binder are the same as those described above.
[0060] In one embodiment of the present invention, the solvent may include an aprotic solvent.
[0061] The aprotic solvent may include one or more selected from the group consisting of anisole, xylene, toluene, N,N'-dimethylacetamide (DMAc), N-methyl pyrrolidone (NMP), dimethyl sulfoxide (DMSO), and N,N-dimethylformamide (DMF).
[0062] In addition, the amount of the solvent may be appropriately adjusted so as to prepare a slurry having a concentration sufficient for smoothly carrying out a coating process, for example, the solvent may be mixed in an amount of 50 to 150 parts by weight based on 100 parts by weight of the solid electrolyte.
[0063] In the method for preparing a solid electrolyte membrane according to the present invention, in step (S2), the slurry may be coated on a substrate and then dried.
[0064] The substrate is not particularly limited as long as it can be used as a substrate during the manufacture of an electrolyte membrane. For example, the substrate may include at least one selected from the group consisting of polyethylene (PE), ethylene vinyl acetate copolymer (EVA), polypropylene (PP), polyimide (PI), polyamide (PA), polycarbonate (PC), polyacrylonitrile (PAN), polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polyethylene terephthalate (PET), polyvinyldifluoroethylene, polyvinyl chloride, polyvinylidene chloride, polyetherketone, polyetheretherketone (PEEK), and polyethylene ether nitrile.
[0065] In addition, the coating method is not particularly limited as long as it is a method capable of forming a coating layer using a slurry, For example, the coating can be performed by roll coating, gravure coating, doctor blade coating, slot die coating, slurry coating, or extrusion coating.
[0066] The drying method is not particularly limited as long as it is a method capable of removing the solvent from the coating layer. For example, the drying may be performed at a temperature of 60 to 130°C. Specifically, the drying temperature may be 60°C or higher, 65°C or higher, 70°C or higher, or 75°C or higher, and may be 85°C or lower, 90°C or lower, 100°C or lower, 110°C or lower, 120°C or lower, or 130°C or lower. A vacuum drying process may also be added. The solvent can be completely removed by the drying.
[0067] In the method for manufacturing a solid electrolyte membrane according to the present invention, in step (S3), the coating layer may be compressed at a temperature equal to or higher than the glass transition temperature (Tg) of the binder.
[0068] In one embodiment of the present invention, the glass transition temperature (Tg) of the binder may be 45 to 250° C., specifically, 45° C. or more, 60° C. or more, 80° C. or more, or 100° C. or more, and 160° C. or less, 180° C. or less, 200° C. or less, 220° C. or less, or 250° C. or less. If the glass transition temperature (Tg) is less than 45° C., the mobility of the binder is not improved, and therefore the packing density is not improved, and therefore the effect of improving ion conductivity is not expected. If the glass transition temperature (Tg) exceeds 250° C., the processability of preparing the solid electrolyte membrane may be reduced.
[0069] In one embodiment of the present invention, the pressure during pressurization may be 300 to 500 MPa, specifically, 300 MPa or more, 320 MPa or more, 340 MPa or more, or 360 MPa or more, and may be 400 MPa or less, 420 MPa or less, 440 MPa or less, 460 MPa or less, 480 MPa or less, or 500 MPa or less.
[0070] If the pressure is less than 300 MPa, the ionic conductivity and strength of the solid electrolyte membrane may be low, and the processability may be reduced. If the pressure exceeds 500 MPa, it may be difficult to apply high pressure due to the limitations of the manufacturing equipment.
[0071] All solid state battery The present invention also relates to an all-solid-state battery comprising the solid electrolyte membrane.
[0072] The all-solid-state battery according to the present invention includes the solid electrolyte membrane; a positive electrode formed on one side of the solid electrolyte membrane; and a negative electrode formed on the other side of the solid electrolyte membrane.
[0073] In an embodiment of the present invention, the positive electrode may include a positive electrode active material, a conductive material, and a binder.
[0074] In the present invention, the positive electrode included in the all-solid-state battery may include a positive electrode active material layer, and the positive electrode active material layer may be formed on one surface of a positive electrode current collector.
[0075] The positive electrode active material layer includes a positive electrode active material, a conductive material, and a binder.
[0076] The positive electrode active material is not particularly limited as long as it is a material capable of reversibly absorbing and releasing lithium ions. For example, lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), Li[Ni x Co y Mn z M v ]O2 (wherein M is any one or more elements selected from the group consisting of Al, Ga, and In; 0.3≦x<1.0, 0≦y, z≦0.5, 0≦v≦0.1, and x+y+z+v=1), Li (Li a M b-a-b’ M' b’ )O 2-c A c (wherein, 0≦a≦0.2, 0.6≦b≦1, 0≦b'≦0.2, 0≦c≦0.2; M includes Mn and at least one selected from the group consisting of Ni, Co, Fe, Cr, V, Cu, Zn, and Ti; M' is at least one selected from the group consisting of Al, Mg, and B, and A is at least one selected from the group consisting of P, F, S, and N); 1+y Mn 2-y Lithium manganese oxides such as LiMnO4 (where y is 0 to 0.33), LiMnO3, LiMn2O3, and LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, LiFe3O4, V2O5, and Cu2V2O7; and the chemical formula LiNi 1-yNi-site type lithium nickel oxide represented by MyO2 (where M=Co, Mn, Al, Cu, Fe, Mg, B or Ga, and y is 0.01 to 0.3); chemical formula LiMn 2-y M y Examples of the lithium manganese composite oxides include, but are not limited to, lithium manganese composite oxides represented by the formula LiMn2O2 (wherein M is Co, Ni, Fe, Cr, Zn, or Ta, and y is 0.01 to 0.1) or Li2Mn3MO8 (wherein M is Fe, Co, Ni, Cu, or Zn); LiMn2O4 in which part of the Li in the chemical formula is replaced with an alkaline earth metal ion; disulfide compounds; and Fe2(MoO4)3.
[0077] The positive electrode active material may be included in an amount of 60 to 80 wt % based on the total weight of the positive electrode active material layer. Specifically, the content of the positive electrode active material may be 60 wt %, 65 wt % or more, or 68 wt % or more, and may be 72 wt % or less, 75 wt % or less, or 80 wt % or less. If the content of the positive electrode active material is less than 60 wt %, the battery performance may be reduced, and if it exceeds 80 wt %, the mass transfer resistance may be increased.
[0078] The conductive material is not particularly limited as long as it prevents side reactions in the internal environment of the all-solid-state battery, does not induce chemical changes in the battery, and has excellent electrical conductivity. Representatively, graphite or conductive carbon may be used, for example, graphite such as natural graphite and artificial graphite; carbon black, acetylene black, ketjen black, denka black, thermal black, channel black, furnace black, lamp black, summer black, etc.; carbon-based materials having a graphene or graphite crystal structure; conductive fibers such as carbon fibers and metal fibers; carbon fluoride; metal powders such as aluminum powder and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives; may be used alone or in combination of two or more kinds, but are not necessarily limited thereto. Preferably, the conductive material may include vapor-grown carbon fiber (VGCF).
[0079] The conductive material may be contained in an amount of 1 wt% to 5 wt% based on the total weight of the positive electrode active material layer. Specifically, the content of the conductive material may be 1 wt% or more, 1.5 wt% or more, or 2 wt% or more, and 4 wt% or less, 4.5 wt% or less, or 5 wt% or less. If the content of the conductive material is less than 1 wt%, the effect of improving electrical conductivity may be difficult to expect, or the electrochemical properties of the battery may be deteriorated, and if the content is more than 5 wt%, the amount of the positive electrode active material may be relatively small, and the capacity and energy density may be reduced. The method of including the conductive material in the positive electrode is not significantly limited, and a conventional method known in the art, such as mixing with the positive electrode active material or coating, may be used.
[0080] The binder is a component that aids in binding the positive electrode active material to the conductive material and the current collector, and is preferably a rubber such as styrene-butadiene rubber, acrylated styrene-butadiene rubber, acrylonitrile copolymer, acrylonitrile-butadiene rubber, nitrile butadiene rubber, acrylonitrile-styrene-butadiene copolymer, acrylic rubber, butyl rubber, fluororubber, polytetrafluoroethylene, polyethylene, polypropylene, ethylene / propylene copolymer, polybutadiene, polyethylene oxide, chlorosulfonated polyethylene, polyvinylpyrrolidone, polyvinylpyridine, polyvinyl alcohol, polyvinyl acetate, polyepichlorohydrin, polyphosphazene, polyacrylonitrile, polybutadiene ... The binder may include one or more selected from the group consisting of polyvinyl chloride, polystyrene, latex, acrylic resin, phenolic resin, epoxy resin, carboxymethyl cellulose, hydroxypropyl cellulose, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl cellulose, cyanoethyl sucrose, polyester, polyamide, polyether, polyimide, polycarboxylate, polycarboxylic acid, polyacrylic acid, polyacrylate, lithium polyacrylate, polymethacrylic acid, polymethacrylate, polyacrylamide, polyurethane, polyvinylidene fluoride, and poly(vinylidene fluoride)-hexafluoropropene. Preferably, the binder may include polytetrafluoroethylene (PTFE).
[0081] In addition, the binder may be included in an amount of 0.5 wt% to 4 wt% based on the total weight of the positive electrode active material layer, and specifically, the binder content may be 0.5 wt% or more, 1 wt% or more, or 1.5 wt% or more, and 3 wt% or less, 3.5 wt% or less, or 4 wt% or less. If the binder content is less than 0.5 wt%, the adhesive strength between the positive electrode active material and the positive electrode current collector may decrease, and if it exceeds 4 wt%, the adhesive strength is improved, but the content of the positive electrode active material may decrease accordingly, and the battery capacity may decrease.
[0082] The positive electrode current collector supports the positive electrode active material layer and transfers electrons between an external conductor and the positive electrode active material layer.
[0083] The positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the all-solid-state battery and has high electronic conductivity. For example, the positive electrode current collector may be made of copper, stainless steel, aluminum, nickel, titanium, palladium, baked carbon, copper or stainless steel surface-treated with carbon, nickel, silver, or the like, or an aluminum-cadmium alloy.
[0084] The positive electrode current collector may have a fine uneven structure or a three-dimensional porous structure on the surface thereof in order to strengthen the bonding force with the positive electrode active material layer, and may have various forms such as a film, a sheet, a foil, a mesh, a net, a porous body, a foam, a nonwoven fabric, etc.
[0085] The positive electrode may be prepared according to a conventional method, specifically, by mixing a positive electrode active material, a conductive material, and a binder in an organic solvent to prepare a composition for forming a positive electrode active material layer, applying the composition onto a positive electrode current collector, drying the composition, and optionally compressing the composition onto the current collector to improve the electrode density. At this time, it is preferable to use an organic solvent that can uniformly disperse the positive electrode active material, the binder, and the conductive material and that can be easily evaporated. Specifically, acetonitrile, methanol, ethanol, tetrahydrofuran, water, isopropyl alcohol, etc. may be used.
[0086] In the present invention, the negative electrode included in the all-solid-state battery may include a negative electrode active material layer, and the negative electrode active material layer may be formed on one surface of a negative electrode current collector.
[0087] The negative electrode active material is lithium (Li +The lithium-containing compound may include a material capable of reversibly intercalating or deintercalating lithium ions, a material capable of reversibly forming a lithium-containing compound by reacting with lithium ions, lithium metal, or a lithium alloy.
[0088] The lithium ion (Li + The material capable of reversibly inserting or de-inserting lithium ions (Li) may be, for example, crystalline carbon, amorphous carbon, or a mixture thereof. + The material capable of reacting with lithium-containing metal oxide (Li) to reversibly form a lithium-containing compound may be, for example, tin oxide, titanium nitrate, or silicon. The lithium alloy may be, for example, an alloy of lithium (Li) and a metal selected from the group consisting of indium (In), sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), francium (Fr), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), radium (Ra), aluminum (Al), and tin (Sn).
[0089] Preferably, the negative electrode active material may be lithium metal or a lithium-indium alloy (Li-In), and more specifically, may be in the form of a lithium metal or lithium thin film or a lithium-indium alloy thin film or powder.
[0090] The negative electrode active material may be included in an amount of 40 to 80 wt % based on the total weight of the negative electrode active material layer. Specifically, the content of the negative electrode active material may be 40 wt % or more or 50 wt % or more, and 70 wt % or less or 80 wt % or less. If the content of the negative electrode active material is less than 40 wt %, the connectivity between the wet negative electrode active material layer and the dry negative electrode active material layer may be insufficient, and if it exceeds 80 wt %, the mass transfer resistance may be large.
[0091] The binder is the same as that described above in the positive electrode active material layer.
[0092] The conductive material is the same as that described above in the positive electrode active material layer.
[0093] The negative electrode current collector is not particularly limited as long as it does not induce a chemical change in the battery and has conductivity, and for example, the negative electrode current collector may be made of copper, stainless steel, aluminum, nickel, titanium, baked carbon, copper or stainless steel whose surface is treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. Similarly to the positive electrode current collector, the negative electrode current collector may be in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc., having fine irregularities formed on the surface.
[0094] The method for manufacturing the negative electrode is not particularly limited, and the negative electrode may be manufactured by forming a negative electrode active material layer on a negative electrode current collector using a method for forming a layer or film commonly used in the art. For example, methods such as compression bonding, coating, deposition, etc. may be used. In addition, the negative electrode of the present invention also includes a case where a thin metallic lithium film is formed on a metal plate by initial charging after assembling a battery without a thin lithium film on the negative electrode current collector.
[0095] Manufacturing method for all-solid-state batteries The present invention also relates to a method for producing an all-solid-state battery.
[0096] The method for manufacturing an all-solid-state battery according to the present invention includes the steps of (P1) placing a mixture for forming a positive electrode active material layer on one side of a solid electrolyte membrane and applying pressure to form a positive electrode on one side of the solid electrolyte membrane; and (P2) placing a negative electrode on the other side of the solid electrolyte membrane and applying pressure.
[0097] In the step (P1), a mixture for forming a positive electrode active material layer may be placed on one side of the solid electrolyte membrane, and then pressurized at high temperature to form a positive electrode on one side of the solid electrolyte membrane.
[0098] The mixture for forming the positive electrode active material layer may include a positive electrode active material, a conductive material, and a binder. The specific types and weights of these are as described above. In addition, after the positive electrode active material layer is formed, a current collector may be attached to the positive electrode to manufacture the positive electrode.
[0099] The pressurizing step is for bonding the solid electrolyte membrane and the positive electrode while reducing the interfacial resistance, and may be performed at a pressure of 300 MPa to 500 MPa. The pressure of the high-temperature pressurizing step may be 300 MPa or more, 350 MPa or more, or 400 MPa or more, and may be 450 MPa or less, 470 MPa or less, or 470 MPa or less. If the temperature and / or pressure of the high-temperature pressurizing step is below the above range, the solid electrolyte membrane and the positive electrode may not be integrated, and if it exceeds the above range, the solid electrolyte membrane or the positive electrode may be deformed or damaged.
[0100] In the step (P2), a negative electrode is placed on the other side of the solid electrolyte membrane and pressurized to manufacture an all-solid-state battery. The negative electrode has been described above.
[0101] The pressure during the pressurization may be 40 MPa to 80 MPa, specifically, the pressure during the pressurization may be 40 MPa or more, 45 MPa or more, or 50 MPa or more, and may be 70 MPa or less, 75 MPa or less, or 80 MPa or less. If the pressure during the pressurization is less than 40 MPa, the interfacial resistance between the negative electrode and the solid electrolyte membrane may increase, and if it exceeds 80 MPa, the solid electrolyte or the negative electrode may be deformed or damaged.
[0102] The all-solid-state battery manufactured in this manner contains a thin solid electrolyte, and therefore the manufacturing cost can be reduced and the ion conductance and energy density can be improved.
[0103] In addition, since the solid electrolyte and the positive electrode are integrated by a high-temperature pressurizing process, the interface stability can be improved.
[0104] Battery Module The present invention also relates to a battery module including the all-solid-state battery as a unit cell, a battery pack including the battery module, and a device including the battery pack as a power source.
[0105] Specific examples of the device include, but are not limited to, power tools that are driven by electric motors; electric vehicles, including electric vehicles (EVs), hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), etc.; electric two-wheeled vehicles, including electric bicycles (E-bikes) and electric scooters (E-scooters); electric golf carts; and power storage systems.
[0106] Below, preferred examples are shown to aid in understanding the present invention. However, the following examples are merely illustrative of the present invention, and it will be apparent to those skilled in the art that various changes and modifications are possible within the scope of the scope and technical ideas of the present invention. Naturally, such changes and modifications also fall within the scope of the appended claims.
[0107] In the following examples and comparative examples, solid electrolyte membranes and all-solid-state batteries were produced according to the compositions and steps shown in Table 1 below.
[0108] [Table 1]
[0109] Example 1 A sulfide-based solid electrolyte (99 wt %) LiPSCl and a binder (1 wt %) SEBS (Styrene-ethylene-butylene-styrene) were mixed and then mixed with a solvent (xylene) to prepare a slurry. At this time, the concentration of the slurry was 67 parts by weight of the solvent per 100 parts by weight of the sulfide-based solid electrolyte.
[0110] The slurry was coated onto a PET (polyethylene terephthalate) release film using a doctor blade and then dried at a temperature of 80°C.
[0111] Thereafter, the coating layer was pressurized at a temperature of 150° C. and a pressure of 370 MPa to produce a solid electrolyte membrane.
[0112] Example 2 A solid electrolyte membrane was produced in the same manner as in Example 1, except that the weight of the SEBS binder was 2% by weight.
[0113] Example 3 A solid electrolyte membrane was produced in the same manner as in Example 1, except that the weight of the SEBS binder was 3% by weight.
[0114] Example 4 A solid electrolyte membrane was produced in the same manner as in Example 1, except that 1 wt % of EVA (ethylene-vinyl acetate) was used as the binder instead of SEBS.
[0115] Example 5 A solid electrolyte membrane was produced in the same manner as in Example 4, except that the weight of the EVA binder was 2% by weight.
[0116] Example 6 A solid electrolyte membrane was produced in the same manner as in Example 4, except that the weight of the EVA binder was 3% by weight.
[0117] Example 7 A solid electrolyte membrane was produced in the same manner as in Example 1, except that the temperature during pressurization was room temperature (25° C.).
[0118] Example 8 A solid electrolyte membrane was produced in the same manner as in Example 2, except that the temperature during pressurization was room temperature (25° C.).
[0119] Example 9 A solid electrolyte membrane was produced in the same manner as in Example 4, except that the temperature during pressurization was room temperature (25° C.).
[0120] Example 10 A solid electrolyte membrane was produced in the same manner as in Example 1, except that the temperature and pressure during pressurization were room temperature (25° C.) and 500 MPa.
[0121] Experimental Example 1: Measurement of packing density and ionic conductivity of solid electrolyte membrane The packing density and ionic conductivity of the solid electrolyte membrane were measured by the following methods.
[0122] (1) Packing density The packing density of the solid electrolyte membrane was calculated using the following formula 1.
[0123]
number
[0124] In the above formula 1, ρ film is the packing density of the solid electrolyte film, and ρ film is the density of the solid electrolyte membrane, and f SE is the weight of the solid electrolyte (SE) contained in the solid electrolyte membrane, and ρ SE is the density of the solid electrolyte (SE) contained in the solid electrolyte membrane, which is an intrinsic physical property of the solid electrolyte material itself, and f Binder is the weight of the binder contained in the solid electrolyte membrane, and ρ Binderis the density of the binder contained in the solid electrolyte membrane and is an inherent physical property of the binder material itself.
[0125] Said ρ film is calculated by the following formula 2.
[0126]
number
[0127] In the above formula 2, ρ film is the density of the solid electrolyte membrane, m is the weight of the solid electrolyte membrane, d is the thickness of the solid electrolyte membrane (μm), and A is the area of the solid electrolyte membrane (cm 2 ).
[0128] (2) Ionic conductivity To measure the ionic conductivity of the solid electrolyte membrane, the solid electrolyte membrane was placed in a polyether ether ketone (PEEK) holder with a diameter of 10 mm, and a titanium rod was used as a blocking electrode to measure the ionic conductivity.
[0129] The resistance was measured using an electrochemical impedance spectrometer (EIS, VM3, Bio Logic Science Instrument) at 25° C. under conditions of an amplitude of 10 mV and a scan range of 1 Hz to 0.1 MHz, and then the ionic conductivity of the solid electrolyte membrane was calculated using the following Equation 3.
[0130]
number
[0131] In the above formula 3, σi is the ionic conductivity (mS / cm) of the solid electrolyte membrane, R is the resistance (Ω) of the solid electrolyte membrane measured by the electrochemical impedance spectrometer, L is the thickness (μm) of the solid electrolyte membrane, and A is the area (cm 2 )
[0132] Table 2 below shows the results of the packing density and ionic conductivity measured by the above-mentioned methods.
[0133] [Table 2]
[0134] Referring to Table 2, it was confirmed that the binder content and ionic conductivity are inversely proportional, and the temperature at the time of applying pressure and ionic conductivity are proportional. In particular, even when a larger pressure was applied at room temperature (Example 10), the ionic conductivity was lower than when the membrane was prepared at a high temperature (Example 1), which shows that applying pressure at a high temperature is important for improving the ionic conductivity of the solid electrolyte membrane.
[0135] In addition, under the same manufacturing process conditions, it can be seen that the ionic conductivity of the solid electrolyte membrane is higher when the SEBS binder is used than when the EVA binder is used (Examples 1 and 4, Examples 2 and 5, or Examples 3 and 6).
[0136] On the other hand, it can be seen that the rate of increase in ionic conductivity due to temperature conditions when pressurized is higher when the EVA binder is used (Examples 4 and 9) than when the SEBS binder is used (Examples 1 and 7, or Examples 2 and 8).
[0137] Although the present invention has been described above using limited examples and drawings, the present invention is not limited thereto, and it is of course possible for a person having ordinary knowledge in the technical field to which the present invention pertains to make various modifications and variations within the technical spirit of the present invention and the equivalent scope of the claims described below. [Explanation of symbols]
[0138] 1: Solid electrolyte membrane 10: Sulfide solid electrolyte 20: Binder 30: Base material
Claims
1. A solid electrolyte membrane comprising a solid electrolyte and a binder, The solid electrolyte includes at least one selected from the group consisting of a sulfide-based solid electrolyte and a halide-based solid electrolyte, A solid electrolyte membrane having a packing density of 0.81 or more and 0.99 or less.
2. The sulfide-based solid electrolyte is represented by the following chemical formula 1: [Chemical formula 1] L a1 M b1 P c1 S d1 A e1 In Chemical Formula 1, L is an element selected from Li, Na, and K, M is an element selected from B, Zn, Sn, Si, Cu, Ga, Sb, Al, and Ge, A is I, Br, Cl, or F, a1 to e1 are composition ratios of each element, and a1:b1:c1:d1:e1 is 1-12:0-1:1:2-12:0-5.
3. The halide-based solid electrolyte is represented by the following chemical formula 2: [Chemical formula 2] Li 6-3a M a Br b Cl c In Formula 1, M is a metal other than Li, a is 0<a<2, b is 0≦b≦6, c is 0≦c≦6, and b+c=6.
4. 2. The solid electrolyte membrane according to claim 1, wherein the solid electrolyte is contained in an amount of 95% by weight or more and 99.5% by weight or less based on a total weight of the solid electrolyte membrane.
5. 2. The solid electrolyte membrane according to claim 1, wherein the binder comprises at least one selected from the group consisting of ethylene-vinyl acetate (EVA), styrene-ethylene-butylene-styrene (SEBS), styrene butadiene rubber (SBR), nitrile butadiene rubber (NBR), hydrogenated nitrile butadiene rubber (HNBR), and copolymers containing the same.
6. 2. The solid electrolyte membrane according to claim 1, wherein the binder is contained in an amount of 0.5 wt % or more and 5 wt % or less based on the total weight of the solid electrolyte membrane.
7. 2. The solid electrolyte membrane according to claim 1, wherein the solid electrolyte is directly bonded to an adjacent solid electrolyte or is bonded to an adjacent solid electrolyte via the binder.
8. 2. The solid electrolyte membrane according to claim 1, wherein the ionic conductivity of the solid electrolyte membrane is 0.1 mS / cm or more and 10 mS / cm or less.
9. (S1) mixing a solid electrolyte, a binder, and a solvent to form a slurry; (S2) coating the slurry on a substrate and then drying it; and (S3) compressing the coating layer at a temperature equal to or higher than the glass transition temperature (Tg) of the binder; The solid electrolyte includes at least one selected from the group consisting of a sulfide-based solid electrolyte and a halide-based solid electrolyte.
10. The solvent comprises an aprotic solvent; 10. The method for producing a solid electrolyte membrane according to claim 9, wherein the aprotic solvent comprises at least one selected from the group consisting of N,N'-dimethylacetamide (DMAc), N-methylpyrrolidone (NMP), dimethylsulfoxide (DMSO) and N,N-dimethylformamide (DMF).
11. 10. The method for producing a solid electrolyte membrane according to claim 9, wherein the binder has a glass transition temperature (Tg) of 45°C or higher and 250°C or lower.
12. The method for producing a solid electrolyte membrane according to any one of claims 9 to 11, wherein the pressure during the pressurization is 300 MPa or more and 500 MPa or less.
13. An all-solid-state battery comprising a positive electrode, a negative electrode, and the solid electrolyte membrane according to any one of claims 1 to 8 interposed therebetween.
Citation Information
Patent Citations
Process of treating molded product, and molded product
JP2004027131A
Polyester flooring material
JP2004196967A
Electrolyte layer for all-solid secondary battery, laminate for all-solid secondary battery, and all-solid secondary battery
JP2010205449A
Nitrile group-containing copolymer rubber
JP2016534173A
All-solid battery
JP2021132005A